Optimalisasi Pendayagunaan Zakat Melalui Program Beasiswa Prestasi Tahun 2017-2020: Studi Kasus pada Dompet Dhuafa Waspada Sumatera Utara - Suri, Atika; Nasution, Annio Indah Lestari; Yanti, Nursantri (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study was conducted to determine whether the utilization of zakat carried out by Dompet Dhuafa Waspada (DDW) in collaboration with UPZ Bank SUMUT throught the achievement scholarship program has been running optimally or not. This study use a descriptive approach with the type of research is qualitative, so the data analysis use is descriptive qualitative analysis. The results of this study indicate that the achievement scholarship program run by DDW in collaboration with UPZ Bank SUMUT has been running optimally. It is evident from the amount of funds obtained since 2017-2020 which has increased, as well as all the efforts they have made to make this program better and more effective. Then this achievement scholarship program has also resulted in significant changes to the lives of the scholarship beneficiaries, starting from the assistance in education costs, increasing skills and knowledge about entrepreneurship. However, there is still a need for further improvements in the implementation of this program so that this program continues to improve and be more optimal.